INFLUENCE OF FRAME WORK STRENGTHENING ON THE STRESS-STRAIN STATE OF TWO-STOREY BUILDINGS OF LOW-STRENGTH MATERIALS - RAZZAKOV, S.J.; KHOLMIRZAEV, S.A. (Stroitelʹnaâ mehanika inženernyh konstrukcij i sooruženij (Online), 2017)
On the basis of the spatial model, the researches of stress-strain state of a two-story building from low-strength material for substantiate the effectiveness of the installation frame were fulfilled. The frame helps to reduce the stress and strain in the load-bearing structures and ensures reliable operation housing in areas with high seismicity. The choice of physical- and-mechanical characteristics for the material of brickwork is realized on the basis of natural experiments. Two models are considered: with strengthening and without strengthening of the walls by the frame. Analysis of a box-typed structure is carried out numerically by FEM.